2019
DOI: 10.1016/j.spa.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Continuum percolation for Cox point processes

Abstract: We investigate continuum percolation for Cox point processes, that is, Poisson point processes driven by random intensity measures. First, we derive sufficient conditions for the existence of non-trivial sub-and super-critical percolation regimes based on the notion of stabilization. Second, we give asymptotic expressions for the percolation probability in largeradius, high-density and coupled regimes. In some regimes, we find universality, whereas in others, a sensitive dependence on the underlying random int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(62 citation statements)
references
References 35 publications
1
61
0
Order By: Relevance
“…A Cox point process X λ with intensity λΛ is characterized by the property that conditional on Λ, X λ is a Poisson point process with intensity λΛ. In [HJC18], it was shown that under certain stabilization and connectedness conditions on Λ, 0 < λ c (r) < ∞ holds. More precisely, λ c (r) > 0 if Λ is stabilizing and λ c (r) < ∞ under the stronger assumption that Λ is asymptotically essentially connected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Cox point process X λ with intensity λΛ is characterized by the property that conditional on Λ, X λ is a Poisson point process with intensity λΛ. In [HJC18], it was shown that under certain stabilization and connectedness conditions on Λ, 0 < λ c (r) < ∞ holds. More precisely, λ c (r) > 0 if Λ is stabilizing and λ c (r) < ∞ under the stronger assumption that Λ is asymptotically essentially connected.…”
Section: Introductionmentioning
confidence: 99%
“…According to [HJC18], the most important examples of Λ for telecommunication are given by a stationary tessellation process, e.g., a Poisson-Voronoi, Poisson-Delaunay or Poisson line tessellation. The edge set of such a tessellation process can be used for modelling a telecommunication network on a street system, where the points of the Cox point process are the users, situated on the streets.…”
Section: Introductionmentioning
confidence: 99%
“…exists, see [HJC18,Lemma 6.1]. This can be used for example to establish the limiting behavior of the percolation probability for the Boolean model with large radii based on Cox point processes where the intensity measure is given by |S ∩ dx|, see [HJC18].…”
mentioning
confidence: 99%
“…There is a possible theoretical gap between H * ≥ H c and the critical value H c ≈ 0.743 found in Section IV-B, however our simulations suggest that H * ≈ H c . A rigorous proof of the above result follows the approach developed in [15]. As the goal of this paper is more about giving numerical estimates, and due to space constraints, we only give a rough sketch of the proof.…”
Section: Relay-and-user-limited Connectivitymentioning
confidence: 99%
“…The main problem faced in the study of percolation in a random environment (PVT street system in our case) is the spatial dependence of the environment. By the stabilization property [15] of the PVT, the configuration of the network environment in a given observation window only depends on a bounded region including the observation window with high probability. In other words, if two observed regions of the network are distant enough, they are independent.…”
Section: Sketch Of Proof Of Theoremmentioning
confidence: 99%